0426 Time Restricted Feeding Consolidates Sleep in the BACHD Mouse Model of Huntington's Disease. (27th May 2020) - Nichols, I S; Chiem, E; Tahara, Y; Anderson, S; Trotter, D; Whittaker, D; Ghiani, C; Colwell, C; Paul, K
Abstract: Introduction: Disturbances in the daily sleep-wake cycle are common in individuals with neurodegenerative disorders. Huntington's disease (HD) is a genetic neurodegenerative disorder in which patients exhibit a variety of impairments that include, poor motor function, disrupted circadian rhythms, and sleep abnormalities such as difficulty initiating sleep at bedtime and more frequent nighttime arousals. In the BACHD mouse model time restricted feeding (TRF) has been successful at improving motor functions and circadian rhythms. The BACHD mouse model has a bacterial artificial chromosome that expresses the full-length human mutant huntingtin gene. Methods: In order to determine the effects of TRF on sleep-wake architecture, EEG/EMG polysomnographic records were examined in mice between 3-4 months old bearing the BAC knock-in of a human genetic mutation of HD and WT litter mates, first during ad libitum (ad lib) feeding then during an 18 hour fasting protocol. TRF protocol consisted of 6 hours of food access limited between ZT15-ZT21 and 18 hours of fasting. Results: A two-way ANOVA revealed that TRF significantly decreased the amount of total sleep (p=0.04) and NREM sleep (p=0.04) in the dark phase in both WT and BACHD mice. TRF did not significantly affect sleep in the light phase, however trends suggest that BACHD mice have more sleep in the light phase under TRF than ad lib. Conclusion: This data suggests that TRF improves sleep by consolidating sleep to the light phase and wake to the dark phase. In conclusion, TRF may be a promising tool that can improve the negative effects of neurodegenerative diseases on sleep-wake processes. Support: These experiments were supported by R01-NS078410 and UCLA start-up funds.